2005
DOI: 10.1177/147323000503300603
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory Blood Pressure Comparison of the Anti-hypertensive Efficacy of Fixed Combinations of Irbesartan/hydrochlorothiazide and Losartan/hydrochlorothiazide in Patients with Mild-to-moderate Hypertension

Abstract: This study examined whether the greater anti-hypertensive efficacy of irbesartan monotherapy over losartan monotherapy extends to the respective fixed-dose combinations with hydrochlorothiazide (HCTZ) in patients with mild-to-moderate hypertension. Patients were treated with either irbesartan 150 mg/HCTZ 12.5 mg or losartan 50 mg/HCTZ 12.5 mg over a 4-week period. Twenty-four hour daytime and night-time mean blood pressure (BP), BP load and duration of action were assessed using ambulatory BP monitoring. Both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 35 publications
2
19
1
2
Order By: Relevance
“…However the relative efficacy from the comparison of substances in monotherapy 7,8,11 is generally maintained for the corresponding combinations with HCTZ. 12,13 These studies showed a greater reduction in blood pressure from 150 mg irbesartan compared with 50 mg losartan 7,11,13 both with and without HCTZ. In a study with losartan 100 mg/HCTZ 25 mg, a reduction in blood pressure of 24.0/11.8 mmHg was achieved at an initial blood pressure of 160.8/94.4 mmHg.…”
Section: Predictor Of Reduction In Blood Pressurementioning
confidence: 99%
“…However the relative efficacy from the comparison of substances in monotherapy 7,8,11 is generally maintained for the corresponding combinations with HCTZ. 12,13 These studies showed a greater reduction in blood pressure from 150 mg irbesartan compared with 50 mg losartan 7,11,13 both with and without HCTZ. In a study with losartan 100 mg/HCTZ 25 mg, a reduction in blood pressure of 24.0/11.8 mmHg was achieved at an initial blood pressure of 160.8/94.4 mmHg.…”
Section: Predictor Of Reduction In Blood Pressurementioning
confidence: 99%
“…In the study by Neutel and Smith, the difference in BP reduction between irbesartan and losartan was statistically significant only for DBP (P ¼ 0.01), perhaps due to the small sample size. However, using the study by Neutel and Smith represents a conservative approach, as the BP reductions with irbesartan in this study are slightly more favourable compared with the BP reductions with irbesartan in Bobrie et al, 28 which means that the relative efficacy of irbesartan compared with losartan may be underestimated if the data concerning losartan from Neutel and Smith 29 are compared indirectly with the data for irbesartan in Bobrie et al…”
Section: Discussionmentioning
confidence: 77%
“…Comparisons between irbesartan and losartan in mild-to-moderate hypertension are available in, for example, Kassler-Taub et al, 47 Neutel and Smith 29 and Oparil et al 48 For the base case analysis, the Neutel and Smith study was used here, even though the sample size is quite small (n ¼ 30). The study by Kassler and Taube did not include combination therapy and used only losartan 100 mg, and in Oparil et al the patients were uptitrated as needed from losartan 50-100 mg or from irbesartan 150-300 mg, and HCTZ was added if the goals were not reached.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Результаты этого исследования свидетельствовали о статистически значимо более выраженном снижении систолического и диастоли-ческого АД при сочетанном приеме 150 мг ирбесар-тана и 12,5 мг ГХТЗ по сравнению с применением 80 мг валсартана и 12,5 мг ГХТЗ: снижение систоли-ческого АД при использовании такой терапии дости-гало 13 и 10,6 мм рт.ст., соответственно, (p=0,0094 для сравнения между группами), а диастолического АД -9,5 и 7,4 мм рт.ст., соответственно, (p=0,0007 для сравнения между группами). Сходные данные были получены и в ходе выполнения другого исследова-ния, включавшего больных со слабовыраженной или умеренной АГ [19]. Его результаты также свидетель-ствовали о более выраженном снижении диастоличе-ского АД, измеренного с помощью 24 ч АД монито-рирования, при сочетанном применении ирбесартана и ГХТЗ по сравнению с приемом лозартана в сочета-нии с ГХТЗ, которое достигало 10,5 и 6,1 мм рт.ст., соответственно, (p=0,001 для сравнения между груп-пами).…”
Section: подходы к выбору антигипертензивного препарата при использовunclassified